The correlations among learning motivation, self-confidence, and writing ability of students descriptive text - Dean May Julian; Baginda Simaibang; Mulyadi Mulyadi (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This thesis was concerned with the inquiry on the correlations among learning motivation, self-confidence, and writing ability of the seventh grade students at State Junior High School of Lubai Ulu Sub-District of Muaraenim Regency. The problem of the study was to investigate the correlation among students’ learning motivation, self-confidence, and writing ability. The total number of the population were 474 students. The sample for this study was 83 students taken through a simple random sampling technique. Data were collected by adopting a questionnaire for learning motivation, self-confidence, and test for writing ability. Data were analyzed by using r-Product Moment and Multiple Regression. Finding showed that: (1) there was significant correlation between learning motivation and writing ability; (2) there was not any significant correlation between self-confidence and writing ability; (3) there was not any significant correlation between learning motivation and self-confidence; (4) there were significant correlations among learning motivation, self-confidence, and writing ability of seventh grade-students at state Junior High School of Lubai Ulu Muaraenim.